O Recrutamento de Libertos para a Guerra do Paraguai: considerações recentes sobre um tema complexo - Vitor Izecksohn (Navigator, 2015)
This paper addresses the issue of military recruitment of freed slaves by the Brazilian armed forces during the War of the Triple Alliance. Emphasis will be given to the Army’s situation and the meaning of such mobilization in the historical context of black military service in the Potuguese-Brazilian tradition.